Flint Hill Nights, Flint Hill Lights - Christy Davis (Symphony in the Flint Hills, 2019)
Introduction: It was the Age of the City. In the fifty years following the Civil War, during the Second Industrial Revolution, eleven million Americans left their rural communities and moved to bustling metropolitan areas.